Avaliação como processo de aprendizagem: uma experiência com o uso de rubrica - Ferraz, Rosina Paula Ferracciú (2019)
This study has as its general objective the reflection on the action of an evaluative proposal as a pedagogical process, the work of conclusion of the course of Visual Communication, through the use of the rubric as an evaluative instrument. The starting point of this research is a classroom practice. This is a qualitative approach research that aims to favor the critical reflection on the evaluative action of the research teacher and author. As a methodology, Thiollent's Action Research (1986) is used and the analyzes were organized through the reflection process of the four actions proposed by Smyth (1992), based on the writings of Freire (1970): describe, inform, confront and reconstruct, allowing reflection on the evaluation experience as a learning process, with emphasis on the use of rubric as an instrument, in the Planning and Development of the Completion of Visual Communication Course curriculum components. The results suggest that this is a planned proposal that integrates learning, assessment and teaching, focused on the needs to clearly communicate aspects related to the student's evaluation process. It was identified that this process favors the communication of more transparent and coherent evaluation criteria in relation to the learning objectives, clarity about the requirements that will be considered in the evaluation and more involved students who review and reassess the work throughout the process. Through the results of the research it was realized that the use of the rubric, in addition to helping students know what they need to do to achieve a certain grade, can help teachers to think carefully and critically about what they are teaching and what Students need to learn by helping them consider what is important to teach and how to determine the levels at which their students will learn what will be taught. By confronting the proposed action, it was understood that it is possible to rethink the action so that it can be used in other contexts. It is believed that the study may encourage other teachers to use the rubric as an evaluative tool and contribute to other research